2004
DOI: 10.1002/syn.20034
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical interaction between dopaminergic and noradrenergic neurons in the medial prefrontal cortex

Abstract: Growing evidence indicates that there is an interaction between the transmission of dopamine (DA) and norepinephrine (NE) in the noradrenergic and dopaminergic projections that converge in the medial prefrontal cortex (mPFC). The effects of the noradrenergic alpha1 and alpha2 receptors and the NE transporters on the DA outflow and those of the dopaminergic D1 and D2 receptors on NE release in the mPFC were investigated. Local infusions of NE (90, 150, and 300 nM) into the mPFC increased the extracellular relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 32 publications
(45 reference statements)
1
39
1
Order By: Relevance
“…Blockade of α 1 adrenoceptor reduces releases of dopamine, serotonin, and norepinephrine in the mPFC, while inhibition of the α 2 adrenoceptor increases the same releases Devoto and Flore. 2006;Pan et al 2004;Pudovkina et al 2001;Weikop et al 2004). Therefore, the paradoxical effects of QTP on norepinephrine, dopamine, and serotonin release in the mPFC are not attributable to the blockade of adrenoceptors.…”
Section: Discussionmentioning
confidence: 88%
“…Blockade of α 1 adrenoceptor reduces releases of dopamine, serotonin, and norepinephrine in the mPFC, while inhibition of the α 2 adrenoceptor increases the same releases Devoto and Flore. 2006;Pan et al 2004;Pudovkina et al 2001;Weikop et al 2004). Therefore, the paradoxical effects of QTP on norepinephrine, dopamine, and serotonin release in the mPFC are not attributable to the blockade of adrenoceptors.…”
Section: Discussionmentioning
confidence: 88%
“…Possibly the slight change by M100907, and absence by MDL 11,939, is due to their differential a1 adrenergic receptor-binding properties (K i ¼ 128 vs 1800, respectively; see Table 1). Local antagonism of adrenergic a1 receptors diminish DA levels in the mPFC (Pan et al, 2004). Nonetheless, selective antagonism of cortical 5-HT2A receptors clearly does not increase basal DA efflux in the mPFC.…”
Section: Discussionmentioning
confidence: 88%
“…While ␣ 1 -adrenoreceptors are mostly postsynaptic, some might also be located presynaptically (Nakadate et al, 2006), and although ␣ 1 -adrenoreceptor activation was initially reported to increase EPSCs in PFC pyramidal neurons (Marek and Aghajanian,1999), recent evidence suggests instead that it suppresses GLU-, AMPA-, and NMDA-induced EPSCs (Kobayashi et al, 2009). Furthermore, locally applied NE increases PFC DA levels, an effect that is inhibited by local ␣ 1 -adrenoreceptor blockade (Pan et al, 2004). Thus it is presently unclear whether the effects of benoxathian were mediated directly by ␣ 1 -adrenoreceptors on callosal neurons or indirectly via a DA-dependent mechanism.…”
Section: Involvement Of Ne and Gabamentioning
confidence: 99%